2021
DOI: 10.3390/tropicalmed6020082
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Antimicrobial Resistance in Surgical Wards at Mulago National Referral Hospital, Uganda, from 2014 to 2018—Cause for Concern?

Abstract: Antimicrobial Resistance (AMR) and Healthcare Associated Infections (HAIs) are major global public health challenges in our time. This study provides a broader and updated overview of AMR trends in surgical wards of Mulago National Referral Hospital (MNRH) between 2014 and 2018. Laboratory data on the antimicrobial susceptibility profiles of bacterial isolates from 428 patient samples were available. The most common samples were as follows: tracheal aspirates (36.5%), pus swabs (28.0%), and blood (20.6%). Kleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
7
5
0
Order By: Relevance
“…This study found a high prevalence of E. coli, P. aeruginosa , and S. aureus . These findings are similar to those of many short-term researcher-driven studies earlier done at MH, which stated a high prevalence of the same species [ 9 15 ]. These species continue to cause the commonest community- and hospital-acquired bacterial infections [ 9 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study found a high prevalence of E. coli, P. aeruginosa , and S. aureus . These findings are similar to those of many short-term researcher-driven studies earlier done at MH, which stated a high prevalence of the same species [ 9 15 ]. These species continue to cause the commonest community- and hospital-acquired bacterial infections [ 9 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to those of many short-term researcher-driven studies earlier done at MH, which stated a high prevalence of the same species [ 9 15 ]. These species continue to cause the commonest community- and hospital-acquired bacterial infections [ 9 15 ]. But, these species could be used as surveillance markers for AMR in this setting as has been shown [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The success of establishing the national AMR surveillance program in Uganda highlights the feasibility of implementing the WHO GLASS program in LMICs. AMR surveillance programs are fundamental in Sub-Saharan African countries such as Uganda for generating antibiograms that can inform the development of treatment guidelines and antibiotic procurement plans and contribute toward standardized reporting [25,26]. Clinicians at surveillance sites can also access bacterial ID and AST results to inform patient care because of the availability of strengthened quality microbiology services.…”
Section: Principal Findingsmentioning
confidence: 99%